In vitro activity of methanolic extract from Lagerstroemia speciosa (Linn. ex. Murray) bark against pathogenic bacteria - Darah Ibrahim, Lai Kok Hoe, Wong Chin Thong, Lim Sheh Hong (Journal of Applied Pharmaceutical Science, 2013)
Crude methanolic extract of Lagerstroemia speciosa barks (Linn. ex. Murray) was subjected to antimicrobial screening including six Gram-positive and eight Gram-negative bacteria. The extract demonstrated significance antibacterial activities on 5 tested bacteria with the inhibition zone ranging from 10-15 mm. The minimum inhibitory concentration (MIC) of the extract was assessed by microdilution method. MIC value of Bacillus spizizenii ATCC6633, Bacillus cereus and Streptococcus coagulase-negative (SCN) was 0.25 mg/ml whilst Bacillus licheniformis and Acinetobacter anitratus showed MIC value of 0.50 mg/ml. However, only B. spizizenii ATCC6633 and B. licheniformis showed the minimum bactericidal concentration (MBC) value of 2.00 mg/ml and 1.00 mg/ml, respectively. The morphological changes of B.spizizenii ATCC6633 and A. anitratus with the treatment of the extract were observed under Scanning Electron Microscope (SEM). The results suggested that the L. speciosa methanolic extract had caused membrane structural degenerations of the cells and finally leading to cell-lysis.
Keywords: Lagerstroemia speciosa, antibacterial activity, Bacillus spizizenii, minimum inhibitory concentration.